2021
DOI: 10.1088/2051-672x/ac15e0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison of near-dry and cryogenically cooled near-dry machining in wire-cut electrical discharge machining processes

Abstract: In this research, the wire wear ratio (WWR), material removal rate (MRR) and surface roughness (SR) of cryogenic cooled near dry wire-cut electrical discharge machining (NDWEDM) is compared with the existing NDWEDM process. Cryogenic cooled and un-cooled molybdenum wires and Inconel 718 alloy have been used as the electrodes and work-material respectively. The novel experimental setup has been fabricated to mix the minimum amount of water with pressurized air as a dielectric fluid. The control variables such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…For all analyses, the confidence interval is set at 0.95 with a margin of error of 5%. The degree of freedom (DM), the sequential sum of the square (SSQ), the adjusted sequential sum of the square (ASSQ), the variance (VE), the F-value, and the percentage of contribution (POC) have been determined based on the standard procedures of the Taguchi technique [31,32]. The residual error for all response parameters has been determined to be less than 5% by Taguchi's analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For all analyses, the confidence interval is set at 0.95 with a margin of error of 5%. The degree of freedom (DM), the sequential sum of the square (SSQ), the adjusted sequential sum of the square (ASSQ), the variance (VE), the F-value, and the percentage of contribution (POC) have been determined based on the standard procedures of the Taguchi technique [31,32]. The residual error for all response parameters has been determined to be less than 5% by Taguchi's analysis.…”
Section: Resultsmentioning
confidence: 99%
“…While increasing the gap voltage, MH and SR are improved and slightly reduced if the voltage is further increased. However, discharge current increases the MH, WLT, and SR due to increasing heat in the machining zone [55,57]. However, it is possible to make the short-circuit problem worse during the high temperature duration [58].…”
Section: Machining Mechanism Of Graphite Powder-argon Gas Assisted De...mentioning
confidence: 99%
“…It was found that the effects of interaction parameters were not significantly contributed on both responses than individual parameters. The equations ( 3)-( 7) are used for Taguchi analysis as follows [25][26][27]. The total sum of square:…”
Section: Experimentationsmentioning
confidence: 99%